2021
DOI: 10.1109/jsen.2021.3075093
|View full text |Cite
|
Sign up to set email alerts
|

Structural Health Monitoring System With Narrowband IoT and MEMS Sensors

Abstract: Monitoring of civil infrastructures is critically needed to track aging, damages and ultimately to prevent severe failures which can endanger many lives. The ability to monitor in a continuous and fine-grained fashion the integrity of a wide variety of buildings, referred to as structural health monitoring, with low-cost, long-term and continuous measurements is essential from both an economic and a life-safety standpoint. To address these needs, we propose a low-cost wireless sensor node specifically designed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…In general, recent developments in electronics, wireless communication and MEMS 1 sensors are making it possible to acquire data in a cost-effective and energy-efficient way. Novel IoT 2 sensors are enabling some new and important research areas for many applications, including Structural Health Monitoring (SHM) and predictive maintenance (Di Nuzzo et al, 2021;Chen et al, 2021). SHM aims to detect anomalies and prevent apparatus faults (Chen et al, 2021;Qu et al, 2019) at low cost and connected to a long term vision of improving performance and/or reducing costs of a particular asset.…”
Section: Recent Developments In Microelectronicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, recent developments in electronics, wireless communication and MEMS 1 sensors are making it possible to acquire data in a cost-effective and energy-efficient way. Novel IoT 2 sensors are enabling some new and important research areas for many applications, including Structural Health Monitoring (SHM) and predictive maintenance (Di Nuzzo et al, 2021;Chen et al, 2021). SHM aims to detect anomalies and prevent apparatus faults (Chen et al, 2021;Qu et al, 2019) at low cost and connected to a long term vision of improving performance and/or reducing costs of a particular asset.…”
Section: Recent Developments In Microelectronicsmentioning
confidence: 99%
“…SHM aims to detect anomalies and prevent apparatus faults (Chen et al, 2021;Qu et al, 2019) at low cost and connected to a long term vision of improving performance and/or reducing costs of a particular asset. Previous analyses have demonstrated the potential of using inexpensive and low power MEMS sensors aerodynamic purposes (Fathima et al, 2021;Di Nuzzo et al, 2021). For example, arrays of MEMS barometers have already been deployed in other application scenarios, namely to aeroplane wings (Raab and Rohde-Brandenburger, 2020) and to cars (Filipskỳ et al, 2017).…”
Section: Recent Developments In Microelectronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-intrusively measuring aerodynamic and acoustic data with minimal aerodynamic influence on blades is still an open challenge -the limitations for the form factor, power consumption and necessary data bandwidth require a highly optimized Internet of Things (IoT) system. Recently IoT wireless devices have been used more and more for Structural Health Monitoring (SHM) to detect anomalies early on [7]. Moreover, in-field monitoring using distributed systems has also been investigated and deployed in previous publications [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies [11,7] demonstrated the potential of using inexpensive MEMS (Micro-ElectroMechanical Systems) and integrated circuits (ICs) for SHM applications, no MEMS arrays of heterogeneous set of sensors are present in the literature, nor in commercial products, for in-field aerodynamic and aeroacoustic analysis on wind turbines. Arrays of MEMS barometers have already been investigated in several other case studies, where clusters of pressure elements have been embedded into surfaces, including airplane wings [12] and cars [13].…”
Section: Introductionmentioning
confidence: 99%